Analysis of air-to-water converter frame using ANSYS simulation - Naufal Waliy Ishlah; Salvatore Johanes Rega; Triwahyudin Rohman; Subekti Subekti (JTTM : Jurnal Terapan Teknik Mesin, 2024)
According to projections made by the Indonesian Institute of Sciences (LIPI), by 2040 every region along Java's northern coast—from Banten to Surabaya and Iswara—will be an urban area vulnerable to water scarcity. As a result, more careful consideration is required. Since air is an endless supply, turning it into water is one way to address the clean water shortage. A good design's structure is one of its essential components. This is because the device's structure must sustain both the renewable energy source and the complete system. By utilizing ANSYS Workbench and theoretical calculations to analyze the maximum stress results, the research aims to ascertain whether the machine frame is safe for usage. In this investigation, the ANSYS 2021 R1 software was used to apply the finite element method to ASTM A36 material under vertical loading. The air-to-water converter mechanism is still safe after simulations were run on its shaft and frame. This is demonstrated by the biggest maximum stress on the shaft (6.2194 MPa) from the ANSYS numerical simulation and the largest maximum stress (0.349 MPa) on the frame, both of which are still below the allowable stress. Furthermore, a 0.9694 difference in safety factor was found between theoretical calculations and shaft simulation, and a 0.1573 difference was found for the frame. The safety factor acquired from the shaft was 1.6043, while the safety factor gained from the frame was 1.6073